IMPROVEMENT OF CUSTOMERS INCOME THROUGH MURABAHAH PRODUCT IN LKS AL-USWAH DISTRICT CIAMIS - Sumadi Sumadi; Frisky Rais Nurhasan (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
This research was conducted to find out the effect of murabahah financing on increasing customer’s income. The study was conducted in one of the fastest-growing syariah financial institutions in LKS Al-Uswah Branch Ciamis. Murabahah financing is one of the productive financing developed at LKS Al-Uswah Branch of Ciamis. The descriptive verivikatif method is used with the correlational research approach (correlational research). This study’s data collection techniques are by questionnaire—the number of samples taken with incidental sampling technique of 30 customers. The data of this research are financial data analyzed with a coefficient of determination and simple linear regression. The paired t-test sample was used to analyze customers’ income before and after financing. The magnitude of murabahah financing effect to increase customer income in this research is 17,3%. In comparison, the rest that is 82,7%, is another factor that can influence the growth of customers’ income besides murabahah financing. Correlation coefficient value included in the category of moderate level of relations that is equal to 0.416, the value of correlation is marked positive (+), meaning the relationship of financing with income increase is unidirectional. So it can be concluded that murabahah financing significantly affects the increase in customer’s income.